2018
DOI: 10.5588/ijtld.17.0893
|View full text |Cite
|
Sign up to set email alerts
|

Burden, spectrum and outcomes of children with tuberculosis diagnosed at a district-level hospital in South Africa

Abstract: Children with TB managed at this district-level hospital were young, and frequently had acute symptoms and substantial comorbidities. Missed opportunities for TB prevention were identified. Linkage to care support resulted in excellent continuation of TB care; however, treatment outcomes could be further improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…At a district-level hospital, comparable results were achieved by only one dedicated lay health care worker for referral support and follow-up, provided surveillance was done by routine clinical personnel; 93 (96%) of child TB cases successfully accessed PHC care and 89 (90%) were matched in the ETR.Net/EDRWeb. 15 In settings where information technology infrastructure is available, automated, electronic processes at hospital discharge could greatly assist with surveillance and linking of important referral processes, but will still rely on personnel at the referral hospital to provide sufficient information and the receiving facility to act on the information. Another potential solution to close this reporting gap would be to mandate all hospitals to report TB data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a district-level hospital, comparable results were achieved by only one dedicated lay health care worker for referral support and follow-up, provided surveillance was done by routine clinical personnel; 93 (96%) of child TB cases successfully accessed PHC care and 89 (90%) were matched in the ETR.Net/EDRWeb. 15 In settings where information technology infrastructure is available, automated, electronic processes at hospital discharge could greatly assist with surveillance and linking of important referral processes, but will still rely on personnel at the referral hospital to provide sufficient information and the receiving facility to act on the information. Another potential solution to close this reporting gap would be to mandate all hospitals to report TB data.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood TB, especially TB in young children, is often diagnosed at hospital level due to challenges faced in specimen collection and diagnosis. 14,15 A retrospective audit of children diagnosed with culture-confirmed TB during 2007-2009 at a large tertiary hospital in Cape Town, Western Cape Province, South Africa, found an overall reporting gap of 38% (101/267); 32% (58/183) among children discharged home to continue TB care. 16 Given the large number of children with TB managed at this hospital (approximately 400 per year) 14 and other referral centres, this underestimation of the burden and spectrum of TB disease can have a considerable impact on resource allocation and service delivery.…”
mentioning
confidence: 99%
“…While the proportion with favorable outcome was below the global target, it corresponds with child TB outcomes in similar settings [16]. Retrospective studies in Nigeria, South Africa and Ethiopia found child TB (confirmed and clinically diagnosed) success rates of 77.4% [17], 78% [18], and 85.5% [19, 20], respectively. We also found a similar favorable proportion among the confirmed child TB cases.…”
Section: Discussionmentioning
confidence: 99%
“…Al igual que lo descrito en otros estudios, dentro de las presentaciones de TBCEP, predominó la TBC pleural, seguida de SNC y linfoganglionar, siendo poco frecuentes la TBC cutánea, ósea y peritoneal 6,7,21 .…”
Section: Discussionunclassified